Media Pembelajaran PAI melalui IRD Batik Motif Daun Taleus Girimis - Indriya (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research focuses on creating research-based works of art carrying the values ​​of Islamic Education. The work created is IRD batik with the KeUlamaan motif of the Taleus Girimis Leaf series which has contributed to the innovation and development of various batik motifs in Indonesia. It is hoped that various developments of this batik motif into various new products and their derivatives can be used as a basis for making new products, one of which is as an educational medium. There are four stages in the method of creating works of art and inventions from an Islamic perspective, namely experimentation, contemplation, embodiment, and purity of heart. From this method the author will develop Islamic batik motifs into new products that contain Islamic religious education. This research was conducted using a qualitative approach, and creator theory with an attempt to describe the reconstruction of the value of Islamic Religious Education in batik motifs. Data collection was carried out through observation, literature study, interviews, and documentation, and was analyzed descriptively. The authors found this in the reconstruction of Islamic Education values ​​which can be applied to a batik motif. The philosophies that can be applied to Islamic Religious Education motifs or decorations include, (1) Islamic Religious Education in an applicative manner through the media of batik motifs; (2) Education is characterized by the values ​​of the teachings of the clergy; (3) batik as the cultural heritage of the Indonesian people should have maintained its sustainability, IRD Batik innovates where the work is as well as educational media,